2006
DOI: 10.1111/j.1600-0781.2006.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band Ultraviolet B 311 nm in the treatment of vitiligo: two right–left comparison studies

Abstract: NB UVB 311 nm has similar repigmentary effects as PUVA. The addition of psoralen does not increase its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 18 publications
3
40
2
2
Order By: Relevance
“…Neste estudo, não foram utilizados medicamentos e pomadas associadas ao tratamento, porém, estudos anteriores, realizados com UVB associado a pomada e/ou medicamentos e somente com o UVB demonstraram que o tratamento associado a outro método é mais e icaz, concluindo, portanto, que eles podem ser um método coadjuvante para o tratamento do vitiligo (17,23,26,27). Middelkamp-Hup et al (26) constataram que a repigmentação foi considerada clinicamente relevante em 72% dos casos de um grupo que fez combinação do UVB com leucotomos P. (cápsula antioxidante), em relação ao grupo que utilizou placebo e UVB.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Neste estudo, não foram utilizados medicamentos e pomadas associadas ao tratamento, porém, estudos anteriores, realizados com UVB associado a pomada e/ou medicamentos e somente com o UVB demonstraram que o tratamento associado a outro método é mais e icaz, concluindo, portanto, que eles podem ser um método coadjuvante para o tratamento do vitiligo (17,23,26,27). Middelkamp-Hup et al (26) constataram que a repigmentação foi considerada clinicamente relevante em 72% dos casos de um grupo que fez combinação do UVB com leucotomos P. (cápsula antioxidante), em relação ao grupo que utilizou placebo e UVB.…”
Section: Discussionunclassified
“…O UVB tem ação direta sobre os queratinócitos, induzindo alterações estruturais e funcionais por meio de fenômenos imunológicos e maior produção de citocinas imunossupressoras que estimulam a migração e proliferação dos melanócitos (15,16). Indicações para a fototerapia com UVB são mais adequadas para psoríase, pitiríase rósea, foliculite pustulosa, pitiríase liquenóide crônica, controle do prurido e vitiligo (15,17,18).…”
Section: D]unclassified
“…This analysis also revealed that PUVA is associated with the highest rates of side effects. On the other hand, El Mofty and colleagues showed that NB-UVB photo therapy had a similar repigmentary effect as PUVA (El Mofty et al, 2006). By comparing these findings, NB-UVB is choice treatment for extensive vitiligo.…”
Section: Phototherapymentioning
confidence: 94%
“…367 A total of seven studies were excluded. [390][391][392][393][394][395][396] The reasons are documented in the full version of the review (see 'Characteristics of excluded studies ' table 367 ). In addition, 13 studies were omitted on the basis that they were awaiting classification and five were ongoing at the time of the review.…”
Section: Randomised Controlled Trials Included In This Reviewmentioning
confidence: 99%